Sir William Petty and some aspects of C17 natural philosophy - Sharp, L (1975)
Today, Petty is most widely remembered as a founder of modern economics. thus his brilliant analysis of the labour theory of value, the role of monopolies, the velocity of circulation and other like concepts helped guide the development of classic economic thought over the ensuing centuries. His second substantial acheivement, at least in the popular mind, depends on the outstanding success of the Down Survey, the first in English history to be organsised along scientific lines, utilising the principle of division of labour. Beyond this, details of his life and his other intellectual pursuits have attracted only marginal interest. His extrodinary career, prolific writing on education, technology medicine and society and his relationship with the broad intellectual movements of the day have often seemed mere curiosities. At best they have been regarded as peripheral adjuncts to that select group of theories which guarantee his status among more orthodox historians. The thesis shows that such judgements are narrow, misleading and unhistorical. Petty's more celebrated ideas become intelligible only when their evolution and context receive detailed attention. This process would itself be misleading if wider historical considerations were excluded. Pre-eminent among such issues is the remarkable efflorescence of natural philosophy between 1640 and l680. These chronological points loosely denote an outstanding period of growth with which Petty was intimately concerned. When closely scrutinised, the relationship between this figure and his environment emerges as one of complex cause and effect. Only by attracting and encouraging two or three remarkable generactions could English natural philosophy gain momentum. In its turn the training of these recruits gave them the motivation and capacity to devise fresh modes of enquiry. It is a paradox of history that, while this movement's dynamic was shortlived, it thereafter survived and eventually grew into a radical force that changed man's understanding of society and the natural world. The main purpose of this work is to describe Petty's experience of this revolution in ideas. Another significant aspect is the light which is cast on current historiographical debate. While it hopefully avoids slavish discussion of such issues, the thesis has been written with these more immediate concerns in mind. For example Petty's utilitarianism , his debt to 'continental' and 'puritan' science, his view of the Royal Society, his role in pro-Restoration natural philosophy, his method and his scientific originality are all examined so as to illuminate contingent historical problems. While not rejecting other modes of research it would seem that Petty's intellectual biography provides an ideal case for testing some general interpretations with the litmus of the particular. The results indicate a more complex picture than many historians have hitherto portrayed. This approach has necessarily dictated the shape of the present monograph. In consequence its detailed biographical account acts as a preface for three chapters of specialised intellectual analysis. Pre-examination of Petty's early life, using fresh manuscript sources, has produced, a wealth of information that fully documents his experience during these vital years. The later achievements and failures are shown to be products of this training which, while not a determinant of fortune, helped him profit from those dynamic situations for which he instinctively sought. Petty's well-known ideas are shown as natural, if not inevitable., consequences of this background and they are joined by others which warrant greater attention and acclaim. Overall, the first chapter gives a new and integrated account of his career stressing its continuity and debt to English and Continetal natural philosophy. Chapter two presents a brief analysis of Petty's views on economic improvement, education, Medicine and technology. This is linked with his early acceptance of Bacon and is shown to be part of a contemporary genre which called for economic renewal, enhanceed productivity and Social regeneration. Perhaps at his most 'puritan' , if not pietistic, over these issues, Petty regarded them as integral parts of a broad plan for social reform. Correct education was essential for every child. Without popular training in applied science and mathematics, self-sustainiing technologies capable of fuelling economic improvement would not spontaneously develop throughout the country. Co-equal with educational reform came the provision of medical facilities for the whole population. Petty saw the need for painstaking research into nosological, aetiological and nutritional factors. Since the value of a skilled worker was already substantial and since this would increase as the economy becane more sophisticated, it was in the nation's best interest to keep him healthy. With this as the cutting edge of his medical views, Petty also expressed genuine concern for his fellow man. The Most important point was that humanitarianism was also a practical necessity. Research into disease would only process through empirical means, and universal health care was the sole means of providing a sufficient number of cases from which to gather data. This research would be carried out in a new type of teaching hospital which Petty described with meticulous care. In addition, the national requirement for doctors would be controlled by the government to ensure a rational distribution of skills throughout the realm. Petty therefore believed that a medical policy based on sound statistics, monitored by the government and supported by effective clinical treatment would eradicate the worst effects of epidemics and malnutrition. The last constituent of his general policy called for systematic development of new machines and techniques. Throughout his life Petty tried to encourage invention for reasons of personal profit and social gain. Brief attention is paid to two of his unsuccessful projects; double-writing and the twin-hulled ship. In eacn case Petty proved himself an original and determined innovator. His comparative failure provides an excellent example of those factors which restricted invention and discouraged the spread of new technology during this period. Chapter three illustrates the link between Petty's career, his belief in improvement and reform and his response to important elements in contemporary natural philosophy. By analysing the genesis and structure of his Discourse of Duplicate Proportion an unusually detailed picture of one seventeenth century work is also obtained. This essay was a synoptic, but unpolished statement of Petty's approach to science and philosophy. Occasioned by an institutional crisis it became a vehicle for defending the Royal Society against vehement criticism. In showing that its research was both scientific and useful, Petty hoped to quell the Society's misguided opponents. The result was an idiosyncratic blend of applied mathematics, utilitarianism, Galilean mechanics and atomistic philosophy. Petty's defensive and didactic purpose limited the works scope in 1674 but now provides the reader with an unparalleled insight into his later attitudes, It also gives an appropriate introduction to his econometric and statistical exercises. The final chapter investigates Petty's empiricism and his mathematical approach to economic and demographic theory. This does not minimise those few outstanding theoretical achievements which have already received widespread acclaim from modern historians. Instead it explores other ideas which were of equal importance to Petty's methodology. By establishing that this was a product of his 'Baconian' philosophy, practical experience and more abstract analytical approach (ultimately derived from Cartesian and continental models) a more judicious assessment of Petty's socio-economic thought is reached, This exposes his careless extrapolation from unreliable data, but shows that such errors were consonant with his deep understanding of the need for accurate social and economic surveys. Fresh evidence proves that Petty tried time and again to gain government support for a national bureau of statistics and. that when these efforts failed he gathered statistical information from every available source. Further evidence shows that he understood how to use this data to reorganise vital elements within the English economy. As always, his projects were constructed with great care and attention to detail. Although at variance with the prevailing political climate they were, without doubt, both farsighted and inherently practical. Given the inevitable limitations of a thesis and the elusiveness of historical evidence, various issues covered by this Chapter have received only limited attention. For example, the perplexing relationship between Petty and Grannt has been examined, but the central problem of authorship remains unsolved. Fresh analysis of this question confirms the current view that both men published their ideas as joint and original contributions to the new discipline of socio- econonic analysis. Unfortunately, a definitive reconstnucbion of their individual roles must await the discovery of manuscripts which may no longer exist. By the end of the enquiry Petty emergies as a leading figure of seventeenth century natural philosophy. The breadth of his interests, his outstanding insight into social, technological, economic and institutional problons and an indonitable, if occasionally unrealistic, drive to implement his ideas guarantee him a place at the side of Boyle, Hewton and Ray. Even his failures show that he possessed unusual creativity and vision. Petty's remarkable career and his personal synthesis of scientific ideas also confound modern attempts to categorise the 'Scie:itific Revolution' under any particular cansal, religious or terminological heading. Only by looking at his as an individual within the context of a larger movement can the pluralisn of both emerge. Finally, we are left with the irony that as a social and scientific prophet Petty was rejected by most of his contemporaries while, three centuries later, his methods and ideas have been vindicated one after the other.